Thermomechanical loads of powerful turbogenerator stator winding insulation in the presence of water cooling defects - Kuchynskyi, Kostiantyn Arturovich; Kensytskyi, O. H. (Національний технічний університет "Харківський політехнічний інститут", 2023)
An analysis of incidents linked to power units’ emergency disconnecting from network as a result of turbogenerators’ malfunction on the NPP of Ukraine is conducted. It is identified, that the reason of the majority of incidents is an insufficient reliability of the stator winding’s direct cooling system. Problem. The most problematic point in winding for today is the frontal parts, where, while cooling is reduced, there are not only thermal, but also thermomechanical loadings on an insulation appearing. The level of these loading depends on structural design of frontal parts and a character of violation of coolant agent circulation in a bar. In some cases they can exceed limit values. The spread and the quality of research on this issue for today are insufficient. Goal. The aim of the completed research is to determine the thermomechanical loading of insulation of stator winding bar in a powerful turbogenerator with a direct liquid cooling under condition when coolant circulation is malfunctioned. Methodology. A complex mathematical model of thermomechanical processes in an insulation of stator winding bar of a powerful turbogenerator is developed. It takes into account the real geometry of the winding bar, variable thermal loading of core elements in radial and axial directions, as well as ways of fixation of slot and frontal winding parts. Studies of thermomechanical processes in an insulation of stator winding bar of turbogenerator are conducted. Results. Values of mechanical displacement and stress for the different modes of malfunction are obtained. Areas of bar, where mechanical loading may exceed the boundaries of mechanical durability of material of insulation of stator winding are identified. With decline of coolant liquid consumption the radial displacement and stress in the winding insulation bar in the area, where the bar exits from the slot are increasing along with that the values of radial stress of insulation of the winding bar in places of frontal parts’ fixation exceed limit values. Practical significance. The offered mathematical models allow to realize calculation experiments and can be used in practice for development and validation of diagnostic systems, analysis, design and investigation of emergency situations during exploitation of turbogenerators on power stations of Ukraine.

Проведено аналіз інцидентів на АЕС України, пов’язаних із аварійним відключенням енергоблоків від мережі внаслідок відмов турбогенераторів. Встановлено, що причиною більшості із них є недостатня надійність системи безпосереднього охолодження обмотки статора. Найбільш проблемним вузлом обмотки на сьогодні є лобові частини, де при порушеннях охолодження окрім теплового виникають термомеханічні навантаження ізоляції. Рівень цих навантажень залежить від конструктивного виконання лобової частини і характеру порушення циркуляції холодоагенту в стержні. В деяких випадках вони можуть перевищувати граничні значення. Кількість і якість досліджень з цієї проблеми на сьогодні є недостатніми. Метою виконаного дослідження є визначення термомеханічних навантажень ізоляції стержня обмотки статора потужного турбогенератора з безпосереднім рідинним охолодженням при порушеннях циркуляції холодоагенту. Розроблена комплексна математична модель термомеханічних процесів в ізоляції стержнів обмотки статора потужного турбогенератора, що враховує реальну геометрію стержня обмотки, змінні теплові навантаження елементів осердя в радіальному та аксіальному напрямках, а також умови закріплення пазової та лобової частин обмотки. Проведені дослідження термомеханічних процесів в ізоляції стержня обмотки статора потужного турбогенератора. Отримані значення механічних переміщень і напружень для різних видів порушень. Встановлені ділянки стержня, на яких значення механічних навантажень при певних умовах можуть перевищувати межі механічної міцності матеріалу ізоляції обмотки статора. Зі зниженням витрати дистиляту збільшуються радіальні переміщення і напруження в ізоляції стержня обмотки в зоні виходу стержня із паза. При цьому значення радіальних напружень в ізоляції в місцях закріплення лобових частин перевищують припустимі значення. Запропоновані математичні моделі дозволяють реалізувати обчислювальні експерименти і можуть бути використані на практиці для створення та відпрацювання систем діагностики, аналізу, моделювання і розслідування аварійних ситуацій при експлуатації турбогенераторів на електростанціях України.
Keywords: turbogenerator; stator winding; water cooling; violation of circulation; thermomechanical loading; турбогенератори; обмотка статора; водяне охолодження; порушення циркуляції; термомеханічні навантаження